2018
DOI: 10.1590/abd1806-4841.20185314
|View full text |Cite
|
Sign up to set email alerts
|

Occupational dermatoses reported in Brazil from 2007 to 2014

Abstract: BackgroundOccupational diseases are very prevalent in the world, especially in developing countries. Occupational dermatoses are responsible for most of these cases. However, epidemiological studies are rare in Brazil.ObjectivesTo verify the panorama of occupational skin diseases in Brazil describing frequencies of work-related dermatoses and their sociodemographic and occupational patterns.MethodsWe used retrospective data from the Notifiable Diseases Information System, (from 2007-2014) tabulated with the Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
(34 reference statements)
1
5
0
3
Order By: Relevance
“…The prevalence rate of self-reported OSDs over the last 12 months was 1.35% in all workers. Although there are differences according to the survey methods, our results were similar to those of developing countries 819. However, such rates were relatively lower than those of developed countries (9.6–17.6%) 56.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The prevalence rate of self-reported OSDs over the last 12 months was 1.35% in all workers. Although there are differences according to the survey methods, our results were similar to those of developing countries 819. However, such rates were relatively lower than those of developed countries (9.6–17.6%) 56.…”
Section: Discussionsupporting
confidence: 72%
“…According to statistics by the Korea Occupational Safety and Health Agency from 1999 to 2007 regarding cause investigations for industrial accidents, OSDs were more commonly observed in male participants (74.2%) 25. In addition, OSD predominantly affected male or female workers in studies conducted in other countries 57192627. Thus, we considered the analysis of gender-related differences in the occurrences of OSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to age, a study reported that there is a higher prevalence of dry eye (up to 4.34%) among men older than 50 years, 24 differently from the results of some studies which found a higher prevalence of occupational dermatitis among individual younger than 50 years of age. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…Também, as mulheres podem apresentar quadros de menor gravidade de DOs, com remissão mais rápida e com melhor prognóstico se comparado aos homens 11 . Outros estudos relatam que o sexo masculino é mais afetado do que o feminino 6,12 . Essas divergências encontradas podem ocorrer devido as diferentes populações estudadas, bem como a susceptibilidade da pele que é influenciada por fatores individuais e sócio-ambientais 8 .…”
Section: Introductionunclassified